2012
DOI: 10.1890/12-0245.1
|View full text |Cite
|
Sign up to set email alerts
|

From migration to nomadism: movement variability in a northern ungulate across its latitudinal range

Abstract: Understanding the causes and consequences of animal movements is of fundamental biological interest because any alteration in movement can have direct and indirect effects on ecosystem structure and function. It is also crucial for assisting spatial wildlife management under variable environmental change scenarios. Recent research has highlighted the need of quantifying individual variability in movement behavior and how it is generated by interactions between individual requirements and environmental conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
270
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(289 citation statements)
references
References 46 publications
(52 reference statements)
13
270
3
Order By: Relevance
“…Migration was defined as a seasonal movement with a return to the place of departure. Analysis of moose populations in Sweden showed a clear latitudinal pattern to their migratory behaviour (Singh et al 2012). The share of seasonal migrants in a population declined from 95 % in northern declined from 103 to 5 km, respectively.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Migration was defined as a seasonal movement with a return to the place of departure. Analysis of moose populations in Sweden showed a clear latitudinal pattern to their migratory behaviour (Singh et al 2012). The share of seasonal migrants in a population declined from 95 % in northern declined from 103 to 5 km, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Some species, such as moose Alces alces, also show high intraspecific variation in dispersal and migratory behaviour. Movement patterns of moose can vary between years and seasons and with the environmental conditions in the areas which they occupy (Singh et al 2012). It has been observed that some moose are able to migrate up to 800 km in Eurasia (Rozhkov et al 2009) and even over 1500 km in North America (Hoffman et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For large-bodied herbivores, the phenology of vegetation is a critical determinant of diet quality (Van Soest 1982, Crawley 1983) that has been linked to diet choice, individual movement and performance (Hjeljord et al 1990, Albon andLangvatn 1992;Herfindal et al 2006;Hebblewhite et al 2008;Mysterud et al 2008;Hamel et al 2009;Martinez-Jauregui et al 2009;Bischof et al 2012;Nielsen et al 2012;Singh et al 2012;Giroux et al 2014, as well as population processes such as survival, reproduction and density-dependence Wang et al 2006;Pettorelli et al 2007;Wittemyer et al 2007. The ability of landscapes to support herbivores is ultimately limited by the total amount of aboveground net-primary production (ANPP) available for consumption (McNaughton et al 1989;Cebrian and Lartigue 2004).…”
Section: Introductionmentioning
confidence: 99%